2019
DOI: 10.20944/preprints201905.0015.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Oncologic Outcomes in Laparoscopic versus Open Surgery for Non-Metastatic Colorectal Cancer: Personal Experience in a Single Institution

Abstract: The oncologic merits of laparoscopic technique for colorectal cancer surgery remain debatable. Eligible patients with non-metastatic colorectal cancer who were scheduled for an elective resection by only one surgeon in a medical institution were randomized to either laparoscopic or open treatment. During this period, total 188 patients received laparoscopic surgery and other 163 patients to open approach. The primary endpoint was cancer-free 5-year survival after operative treatment and secondary endpoint was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Results from previous studies have shown that laparoscopic lateral pelvic lymphadenectomy for rectal cancer has less perioperative blood loss and fewer postoperative complications compared with open lateral pelvic dissection [5]. There was no difference in the oncological outcomes between the two techniques [6].…”
Section: Comparison With Other Methodsmentioning
confidence: 87%
“…Results from previous studies have shown that laparoscopic lateral pelvic lymphadenectomy for rectal cancer has less perioperative blood loss and fewer postoperative complications compared with open lateral pelvic dissection [5]. There was no difference in the oncological outcomes between the two techniques [6].…”
Section: Comparison With Other Methodsmentioning
confidence: 87%